1997
DOI: 10.1111/j.1540-8159.1997.tb04809.x
|View full text |Cite
|
Sign up to set email alerts
|

Band‐Limited Morphometric Analysis of the Intracardiac Signal: Implications for Antitachycardia Devices

Abstract: Inappropriate electrical therapy and power efficiency play a major role in algorithm implementation for antitachycardia devices (ATD) that capture, store, and analyze the patient electrogram as an adjunct to rate determination. Morphologically based algorithms have been demonstrated to improve specificity, thereby decreasing occurrences of inappropriate electrical therapy. However, morphologically based algorithms are power demanding. Optimization of power efficiency can be achieved by eliminating unnecessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Morphology algorithms were not applied in early ICDs because the required calculations exceeded the capability of the devices' microprocessors. As device technology has improved, morphology algorithms for rhythm discrimination have been implemented by most device manufacturers in both single‐ and dual‐chamber ICDs 18–22 …”
Section: Editorial Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphology algorithms were not applied in early ICDs because the required calculations exceeded the capability of the devices' microprocessors. As device technology has improved, morphology algorithms for rhythm discrimination have been implemented by most device manufacturers in both single‐ and dual‐chamber ICDs 18–22 …”
Section: Editorial Commentmentioning
confidence: 99%
“…As device technology has improved, morphology algorithms for rhythm discrimination have been implemented by most device manufacturers in both single-and dual-chamber ICDs. [18][19][20][21][22] Dual-chamber detection algorithms improve tachycardia discrimination by analyzing the relation between atrial and ventricular activity. Aside from making sense intuitively, dual-chamber detection has been reported to be superior to single-chamber detection by some, but not all, recent clinical trials.…”
mentioning
confidence: 99%
“…Consequently, while T waves are filtered, avoiding oversensing and consequent mismatch with the template, depolarization characteristics are completely preserved. In addition, Morris et al 17 stated that different types of morphometric analyses of bipolar intraventricular electrograms appear to be achievable using bandlimited data and reduced sampling rates that usually occur with implantable devices. In regard to signal processing performed by the ICD, signal filtering does not particularly affect R wave morphology as the frequency band of short-gap bipole (D , 1cm) and integrated sensing systems, which is typically found in the range 10-50 Hz, 21,22 is accommodated by the band-pass of the device.…”
Section: Morphology Discrimination Algorithm Characteristicsmentioning
confidence: 99%
“…The theoretical underpinnings of rhythm discrimination based on bipolar electrograms has been described. [14][15][16][17] The aim of the present study was to evaluate the diagnostic accuracy of the new morphology discrimination algorithm for enhanced rhythm discrimination. This algorithm was tested on induced atrial fibrillation and atrial and ventricular paced rhythms (simulating supraventricular and ventricular tachyarrhythmias) during acute invasive testing performed at predischarge, and upon spontaneous supraventricular and ventricular tachyarrhythmias occurring during follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…25, 26 Tuzcu et al reported the efficacy of the changeable high-pass filter function as one of the methods to avoid sensing failure. 27 In this study, we demonstrated the excellent predictors for T wave oversensing using the existence of Brugada syndrome and the T/R ratio during AAI pacing by the Biotronik ICDs.…”
Section: Efficacy Of the Changeable High-pass Filter Settings In The mentioning
confidence: 99%